АҲОЛИНИ СИФАТЛИ ЁҒ- МОЙ МАҲСУЛОТЛАРИ БИЛАН ТАЪМИНЛАШ МУАММОЛАРИ (Scientific journal of the Fergana State University, 2023)
Thе article presents new theoretical recommendations on improving the quality of plantseed oil in Uzbekistan for prespective reforms in fatty oil industry.